Inverse relation between diastolic blood pressure and long-term outcomes in patients undergoing pharmacoinvasive therapy for myocardial infarction: The J-shaped relation in the contemporary era of revascularisation - Lee, C.H. (2011)
10.2459/01.JCM.0000250868.71154.05